A 1, 8-naphthalimide-based turn-on fluorescent probe for imaging mitochondrial hydrogen peroxide in living cells. (2nd December 2018) - Dai, Fang; Jin, Fang; Long, Ying; Jin, Xiao-Ling; Zhou, Bo
Abstract: Hydrogen peroxide (H2 O2 ) produced from mitochondria has attracted much attention on account of its physiological and pathological functions. Therefore, monitoring mitochondrial H2 O2 levels in living cells is of great significance for understanding its functions. We report here a mitochondria-targeted H2 O2 probe, Mito-HP, which was designed based on the 1, 8-naphthalimide fluorogen by incorporation of a triphenylphosphonium targeting group and a boronate-based molecule switch. The probe demonstrates desired properties such as high selectivity, "turn-on" fluorescence response, excellent water solubility and physiological pH-response along with low cytotoxicity. Fluorescence colocalization studies indicate that the probe is capable of targeting the mitochondria of HeLa cells and is sensitive to the exogenous and endogenous production of H2 O2 with a turn-on fluorescence increase.